(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article scientifically analyzes the immunological significance of breastfeeding in the care of newborns. The composition of breast milk-including immunoglobulins, lysozyme, lactoferrin, interferon, and other bioactive components is examined for its protective role against infections in infants. Compared to artificial feeding, breastfeeding is shown to enhance immune system development, maintain intestinal microbiota balance, and reduce the risk of allergic diseases. The findings highlight that breast milk serves not only as a nutritional source but also as a vital component of immunobiological protection for newborns.